DETURKIFIKASI DALAM TAFSIR HAK DINI, KUR’AN DILI KARYA ELMALILI HAMDI YAZIR - Achmad Yafik Mursyid (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
The transition from the Ottoman Empire to the Republic of Turkey left a long debate between Ulama (Islamic scholars) and the proponents of this system. This transition also affected Turkish religious life patterns with the emergence of "Turkification" efforts. Religious aspects were changed in Turkish. In the context of this debate, Hak Dini Kur'an Dili, the work of Elmalili Hamdi Yazir, appeared. Hamdi Yazir's tendency, as the author of this book, towards the process of the Ottoman transition to the Republic of Turkey, with all its consequences, becomes interesting to research further. To decipher interests that are probably inserted in the color of his interpretation, this study uses the philosophical hermeneutics method of Hans-Georg Gadamer. This research concludes that Hamdi Yazir's activeness in the parliament of the Republic of Turkey did not necessarily make his interpretation according to the objectives to be achieved by the Turkish government when initiating the making of this work. Hamdi Yazir preferred to restrengthen people's understanding of basic Islamic knowledge through interpretation. More than that, through this interpretation, Hamdi Yazir also responded to the achievements of modernization in interpreting related verses. Hamdi Yazir's tendency towards the classical study approach, in the process of interpretation, was influenced by his prejudices. Yazir wanted the interpretation that resulted, can provide understanding for Turkish society that he viewed having experienced degradation in religious understanding. This was committed by Yazir as a form of resistance to the Turkification efforts carried out by the Turkish secular government.